Don't Stare at Me! Exploring the Lived Experiences of Adults with Disability - Ritu Singh; Dr. Geeta Chopra (The Center for Disability Studies and Services Brawijaya University, 2018)
The spirit of rights based approach calls for the meaningful involvement of people with disabilities in daily aspects of life and their participation is crucial if we want to build an inclusive and prosperous society. For achieving the aim of inclusion it becomes necessary to go by the slogan of disabled people's organizations i.e. Nothing about us, without us; this further defines the purpose of present paper which locates the perspectives of people with disabilities in terms of what it means to live with a disability. Much has been focussed on the opinions of caregivers when it comes to talking about people with disabilities thus keeping aside the insider's perspectives of living the phenomenon of disability. The lived experiences of people with disabilities is the need of an hour when across the globe thrust in on inclusion. The paper explores the identity, self-concept, self-consciousness, participation, sexuality, barriers, and employment, all seen through the eyes of the adults with disability. The adults with disabilities feel themselves as normal, want to be included by participating in social and economic domains and explore sexuality as non-disabled people; it is the presence of the barriers in social and environmental zones that hinder their inclusion. The databases searched included Google Scholar, Science Direct, Scopus, Elsevier, Proquest, Springer, and Sage; also the reference lists of journal articles were located.